2018
DOI: 10.1136/bmjsem-2015-000085
|View full text |Cite
|
Sign up to set email alerts
|

Inferior heel pain in soccer players: a retrospective study with a proposal for guidelines of treatment

Abstract: BackgroundThe cause of heel pain among soccer players is multifactorial and is related to repetitive microtrauma due to impact forces involving technical moves, but also the playground, the exercise mode, the recovery time, the climatic conditions and the footwear used.AimTo investigate the aetiology of plantar heel pain of soccer players with the objective of proposing an example of guidelines for treatment.MethodsWe investigated the prevalence and characteristics of inferior heel pain of 1473 professional, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…We found only one study in which the authors [ 27 ] investigated the prevalence and characteristics of lower heel pain in 1473 professional, semi-professional and amateur soccer players. The authors [ 34 ] concluded that lower heel pain among soccer players was primarily caused by local biomechanical stress, although they also found other causes such as sural nerve compression [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found only one study in which the authors [ 27 ] investigated the prevalence and characteristics of lower heel pain in 1473 professional, semi-professional and amateur soccer players. The authors [ 34 ] concluded that lower heel pain among soccer players was primarily caused by local biomechanical stress, although they also found other causes such as sural nerve compression [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Plantar heel pain is a highly prevalent condition accounting for between 20% and 39% of lower-extremity painful disorders affecting both athletic 1,2 and nonathletic 3 populations. Conservative treatment represents the first therapeutic line for this condition.…”
mentioning
confidence: 99%
“…However, in many cases, authors did not distinguish ab initio between professional and nonprofessional athletes, and in many other studies, results were presented mixing the 2 categories. 9 , 21 , 23 , 28 Because of this, the meticulous application of exclusion criteria led to their removal, although this induced us to think that a relevant amount of data might remain hidden because of nonoptimal study designs. Second, in the analysis of treatments for plantar fasciitis, we were not surprised to verify that nonsurgical treatment was the most frequent choice among authors, 13 , 25 , 26 but we expected to find a greater number of studies documenting the results of different treatment strategies.…”
Section: Discussionmentioning
confidence: 99%